2011
DOI: 10.3746/jkfn.2011.40.9.1285
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Sponge Cake with Added Lotus Leaf and Lotus Root Powders

Abstract: This study was conducted to evaluate the effect of lotus leaf and lotus root powder on the quality characteristics of sponge cake. Percentages of 4, 8 and 12% of two kinds of lotus powder were added to the batter based on flour content. Baking and cooling loss rate, volume and specific loaf volume, crumb color, texture, scanning electron microscopy (SEM) and sensory evaluation of the products were analyzed. The baking and cooling loss rate of the control was lower than cakes with added lotus leaf and lotus roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Furthermore, distorted outlines on the surface of starch granules appeared due to weak and thin gluten network. Similar results of SEM were reported by Kim et al (2011),…”
Section: Scanning Electron Microscopy Of Flatbreadsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, distorted outlines on the surface of starch granules appeared due to weak and thin gluten network. Similar results of SEM were reported by Kim et al (2011),…”
Section: Scanning Electron Microscopy Of Flatbreadsupporting
confidence: 91%
“…Kumari et al (2020) reported similar observations for the samples of flatbread made from bio-fortified colored wheat (blue, purple and black) flour. Another study confirmed our observations when lotus root powder (4% to 12%) was used to replace WF in sponge cake (Kim et al 2011). This may be attributed to the browning reactions which occurred during baking.…”
Section: Appearance and Textural Characteristicssupporting
confidence: 81%
See 1 more Smart Citation
“…Lotus (Nelumbo nucifera), a perennial submerged vegetation of southern Asia and northern Australia origin [10] , contains abundant levels of polyphenolic compounds. Lotus roots, a popular vegetable since ancient times, possess antifungal, anti-inflammatory, and anti-anxiety activities.…”
Section: Introductionmentioning
confidence: 99%